Primary Retroperitoneal Ganglioneuroma: A Retrospective Cohort Study of 32 Patients - Xiao, Jianchun; Zhao, Zixuan; Li, Binglu; Zhang, Taiping (Frontiers in Surgery, 2021)
Purpose To investigate the clinical characteristics, diagnosis, differential diagnosis, therapy options and outcomes of retroperitoneal ganglioneuroma. Methods In this retrospective study, we collected and analyzed the clinical data of 32 patients diagnosed with retroperitoneal ganglioneuroma and admitted to Peking Union Medical College Hospital from October 2012 to August 2019. Results Among our 32 cases with retroperitoneal ganglioneuroma, the male-to-female ratio was 1:3 and the mean age was 35. Only 25% of the cases presented with abdominal pain while more than 65% had no specific symptoms. The masses could be found through physical examination in only 5 patients. Most of the tumors located near renal area. They were usually single and displayed an embedded growth pattern with diameters less than 10cm, clear borders and soft texture. For radiological imaging, the majority of tumors demonstrated soft tissue density with mid-to-moderate enhancement on CT imaging and showed hypoecho with moderate blood flow signals in ultrasound. No significantly abnormal laboratory examinations were found in most patients. Of all the 32 patients, 2 chose surveillance after biopsy due to difficulties in operation, while others chose surgical resection. The mean follow-up time was 15.8 months among 26 patients. The tumor stayed stable in the surveillance cases. Residual tumors were found in 4 cases receiving operations with no progress and discomfort. No recurrence was seen in all patients. Conclusions The retroperitoneal ganglioneuroma is a benign tumor without specific clinical manifestations or significant laboratory findings. Typically, it is shown as low density with a clear border and an embedded growth pattern in radiological imaging. The overall prognosis is good. Surgery is an effective approach with possible severe complications. Incomplete resection or surveillance can be considered for some cases that are difficult to get complete resection.